2020
DOI: 10.1021/acscatal.0c02648
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Performance-Limiting Deep Traps in Ta3N5 for Solar Water Splitting

Abstract: Ta3N5 is a promising semiconductor for solar-driven photocatalytic or photoelectrochemical (PEC) water splitting. However, the lack of an in-depth understanding of its intrinsic defect properties limits further improvement of its performance. In this study, comprehensive spectroscopic characterizations are combined with theoretical calculations to investigate the defect properties of Ta3N5. The obtained electronic structure of Ta3N5 reveals that oxygen impurities are shallow donors, while nitrogen vacancies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 55 publications
2
76
0
2
Order By: Relevance
“…Fu et al proposed that Ta 3+ was the most detrimental to the water‐splitting performance of Ta 3 N 5 . [ 92 ] The authors used low‐temperature photoluminescence (PL) spectroscopy to evaluate the effect of deep trap states. They assigned a peak in PL spectra at 730 nm to V N and the other peak at 830 nm to Ta 3+ by the difference of NH 3 flow rate dependence.…”
Section: Problems Limiting Sth Efficiency Of Tandem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fu et al proposed that Ta 3+ was the most detrimental to the water‐splitting performance of Ta 3 N 5 . [ 92 ] The authors used low‐temperature photoluminescence (PL) spectroscopy to evaluate the effect of deep trap states. They assigned a peak in PL spectra at 730 nm to V N and the other peak at 830 nm to Ta 3+ by the difference of NH 3 flow rate dependence.…”
Section: Problems Limiting Sth Efficiency Of Tandem Cellsmentioning
confidence: 99%
“…c) Schematic diagram of the energetic structure of Ta 3 N 5 with O N , V N , and Ta 3þ defects. Reproduced with permission [92]. Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%
“…In addition, Li and co‐workers have suggested that the presence of deep hole traps, arising from the presence of N vacancies, may also contribute to this process. [ 239 ] Current work on Ta 3 N 5 therefore is focused on surmounting the twin challenges of stability and relatively late onset potential.…”
Section: Materials Choice For Pec Water Splittingmentioning
confidence: 99%
“…Several studies have ascribed this signal to the transition from the conduction band edge ( E CB ) to shallow acceptor levels that lie near the valence band edge ( E VB ) [24, 26, 27] . Figure 2 c shows an estimate of the energy band positions including the location of the traps [28] . Figures 2 a,b displays the PL spectrum in terms of potential for the sake of comparison with LSVs (Figure S10).…”
Section: Figurementioning
confidence: 99%